Inkheart [videorecording (Blu-Ray)] - Softley, Iain; Pokorny, Diana; Funke, Cornelia, 1958-; Lindsay-Abaire, David; Fraser, Brendan, 1968-; Bettany, Paul, 1971-; Mirren, Helen; Broadbent, Jim; Serkis, Andy; Navarrete, Javier, 1956-; Funke, Cornelia, 1958- (New Line Home Entertainment ; Distributed by Warner Home Video, 2009)
When Mo Folchart reads a story aloud, the characters leap off the page. Literally. And that's a problem. One night he brings out three characters from Inkheart, a story set in medieval times and filled with magical beings. Capricorn and Basta are two villains. Dustfinger is a fire-eater. Now, 10 years later Mo's daughter, Meggie, discovers the truth and it's up to her to escape Capricorn's evil grasp. Mo has been searching for a long lost book that will help so he can use his special powers to the interlopers back to their world.